2019
DOI: 10.1002/ejoc.201801430
|View full text |Cite
|
Sign up to set email alerts
|

Use of Imidazo[1,2‐a]pyridine as a Carbonyl Surrogate in a Mannich‐Like, Catalyst Free, One‐Pot Reaction

Abstract: Derivatization of imidazo[1,2‐a]pyridine scaffolds have gained considerable attention due to the biological significance of therapeutics based on the imidazopyridine core. By utilizing a catalyst‐free, “Mannich type” reaction, we developed a simple and efficient protocol to aminomethylate the C‐3 position of imidazo[1,2‐a]pyridine through a multicomponent, decarboxylation reaction involving imidazo[1,2‐a]pyridine, a secondary amine, and glyoxylic acid. The developed protocol requires mild reaction conditions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Mannich bases are versatile synthetic building blocks, which can be easily yielded into a range of potential derivatives to be employed in the field of medicinal chemistry . These derivatives have been synthesized through various methodologies described in the bibliography . A large number of Mannich base derivatives with potential antiparasitic activity have been reported .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Mannich bases are versatile synthetic building blocks, which can be easily yielded into a range of potential derivatives to be employed in the field of medicinal chemistry . These derivatives have been synthesized through various methodologies described in the bibliography . A large number of Mannich base derivatives with potential antiparasitic activity have been reported .…”
Section: Introductionmentioning
confidence: 98%
“…[6][7] These derivatives have been synthesized through various methodologies described in the bibliography. [7][8][9][10][11] A large number of Mannich base derivatives with potential antiparasitic activity have been reported. [7,[12][13] In addition, our research group also reported the high potential trypanocidal activity of different Mannich bases.…”
Section: Introductionmentioning
confidence: 99%
“…Functionalization of heterocyclic compounds is an important class of organic reactions due to their existence in a wide range of drugs, vitamins, natural products, biologically active molecules, etc [6] . Among the various heterocyclic compounds, imidazo[1, 2‐ a ]pyridine is the structural unit of a large number of natural and pharmaceutical products [7,8] . The methodology for the synthesis of this bio‐active scaffold includes cyclocondensations,oxidative couplings, rearrangements, C−H functionalizations,carbene‐transformations,multicomponent and tandem reactions among the different substrates [9–14] .…”
Section: Introductionmentioning
confidence: 99%